Maritime issues in the South China Sea troubled waters or a sea of opportunity - Hu, Nien-Tsu Alfred; McDorman, Ted L. (Routledge, 2013)
South China Sea (SCS) issues are complex and dynamic,ranging from historic claims to present day military occupation, from military security to regional stability, from rhetorical appeasements to national interests, from intraregional competition to extraregional involvement. The submissions made in 2009 by several Southeast Asian states to the United Nations Commission on the Limits of the Continental Shelf (CLCS) respecting outer limits of extended continental shelves beyond 200 nautical miles in the South China Sea resulted in renewed attention to the maritime disputes over the insular features and the waters of the South China Sea among several claimant States. Questions have resurfaced about the future of cooperation in the region. Furthermore, the improvement of cross-Strait relations between Taiwan and China after 2008 has added a new element to the evolution of South China Sea issues. This book describes these recent developments in depth and provides an examination of possible future developments in the South China Sea